Identification of Slip Surfaces Using the Geoelectric Imaging Method in the Kalirejo Area, Kokap District, Yogyakarta, Indonesia - Rizqi Prastowo; Hurien Helmi; Obrin Trianda; Rofiqul Umam (STKIP Singkawang, 2021)
Landslides are a significant threat to the environment, infrastructure, and human activity, especially in mountainous and hilly areas. It is, therefore, important to accurately identify the social movements that trigger these processes. The resistivity method can investigate subsurface geological variations, including the potential for landslides. This research was conducted to investigate the subsurface structures in the Kalirejo Village area, Kokap District, Kulon Progo Regency, Yogyakarta regarding identifying the sliding location. This investigation includes five lines of tomographic geoelectric measurements. The results show that the slips surface is at a depth of about 5-10 m with a high resistivity value and the landslide material is weathered soil, and the slip surface is andesite. The resistivity of andesite in range 668-1600 Ωm. The landslide material's thickness is around 5-8 m with resistivity in the range 4,01-22.1 Ωm. Landslide material is water-saturated soil.